PBIS in Texas Juvenile Justice Department's Division of Education and State Programs: Integrating Programs and Developing Systems for Sustained Implementation - Lopez, Amy; Williams, Jerome K.; Newsom, Kimbla (Residential treatment for children & youth, 2015)
This article describes how the Texas Juvenile Justice Department is implementing Positive Behavior Interventions and Supports (PBIS) in its state-level secure facilities. This initiative began in 2009 with the passage of state legislation that requires the agency to pursue a multi-tiered model of support for reading and behavior in the school programs of the state facilities. Positive outcomes during the early stages of implementation led to the adoption of PBIS as the facility-wide behavior management framework for all state facilities. In this article, we describe the history, development, implementation, and current status of PBIS in Texas state-level secure care facilities for juvenile offenders.